Modeling the Potential Geographic Distribution of Black Pepper (Piper nigrum) in Asia Using GIS Tools - Chao-yun HAO; Rui FAN; Milton Cezar Ribeiro; Le-he TAN; Hua-song WU; Jian-feng YANG; Wei-quan ZHENG; Huan YU (Journal of Integrative Agriculture)
Known as the “king of spices”, black pepper (Piper nigrum), a perennial crop of the tropics, is economically the most important and the most widely used spice crop in the world. To understand its suitable bioclimatic distribution, maximum entropy based on ecological niche modeling was used to model the bioclimatic niches of the species in its Asian range. Based on known occurrences, bioclimatic areas with higher probabilities are mainly located in the eastern and western coasts of the Indian Peninsula, the east of Sumatra Island, some areas in the Malay Archipelago, and the southeast coastal areas of China. Some undocumented places were also predicted as suitable areas. According to the jackknife procedure, the minimum temperature of the coldest month, the mean monthly temperature range, and the precipitation of the wettest month were identified as highly effective factors in the distribution of black pepper and could possibly account for the crop's distribution pattern. Such climatic requirements inhibited this species from dispersing and gaining a larger geographical range.